PENERAPAN STRATEGI "PENGALAMAN PENTING" DALAM MENULIS SURAT PRIBADI DENGAN MEDIA TAYANG VIDEO KALEIDOSKOP PADA SISWA KELAS VII SMP NEGERI 40 BANDUNG TAHUN AJARAN 2016/2017 - Sukmawening, Nabila (2017)
This research was conducted to find out the influence of learning strategy critical incident to student learning outcomes. Teachers play an critical incident role in the learning process through learning. For that teachers need to create conditions that enable the process of good interaction with students so that they can perform various learning activities effectively. Furthermore, the level of student learning activeness in a learning process is also a benchmark of the quality of learning itself. The purpose of this study is to describe the comparison between experimental class and kontrol class applying important experience strategy with video kaleidioscope media can improve student learning result of class VII-F as experimental class and VII-G as a weighing class, for Indonesian subjects by their way Write a personal letter in SMP Negeri 40 Bandung, School Year 2016-2017. The research method used is quasi experiment with research design one group pretest posttest design. Instruments used are tests both pretest and posttest, observation and documentation. The result of this research is that teacher teaching strategy based on important experience strategy is very helpful for students to understand the subject matter presented by the teacher and improve the students' learning outcomes while the two classes only reach 38 and 37 only. With an important experience strategy students are able to criticize the important experiences their friends have experienced or experienced and then pour into personalized letters that they will send to someone who they think can share stories of important experience. The result of student learning has an effect on the achievement of minimum mastery criteria in Indonesian Language lesson. -------- Penelitian ini dilakukan untuk memaparkan adanya pengaruh strategi pembelajaran pengalaman penting terhadap hasil belajar siswa. Guru perlu menciptakan kondisi yang memungkinkan terjadinya proses interaksi yang baik dengan siswa agar mereka dapat melakukan berbagai aktivitas belajar dengan efektif. Selanjutnya tingkat keaktifan belajar siswa dalam suatu proses pembelajaran juga merupakan tolok ukur dari kualitas pembelajaran itu sendiri. Tujuan penelitian ini adalah untuk mendeskripsikan adanya perbandingan antara kelas ekperimen dengan kelas kontrol menerapkan strategi pengalaman penting dengan media video kaleidoskop dapat meningkatkan hasil belajar siswa kelas VII-F sebagai kelas ekperimen dan VII-G sebagai kelas kontrol, untuk mata pelajaran Bahasa Indonesia dengan cara mereka menuliskan surat pribadi di SMP Negeri 40 Bandung, Tahun Ajaran 2016-2017. Metode penelitian yang digunakan adalah eksperimen semu dengan rancangan penelitian one group pretest posttest design. Instrumen yang digunakan adalah tes baik pretest maupun posttest, observasi dan dokumentasi. Hasil penelitian ini adalah bahwa strategi mengajar guru berdasarkan strategi pengalaman penting sangat membantu siswa dalam memahami materi pelajaran yang disampaikan oleh guru dan meningkatkan hasil belajar siswa nilai kedua kelas hanya mencapai 38 dan 37. Dengan strategi pengalaman penting siswa mampu mengkritisi pengalaman penting yang pernah dialami ataupun dialami temannya kemudian mereka tuangkan kedalam surat pribadi yang akan mereka kirim kepada seseorang yang menurutnya dapat berbagi cerita pengalaman pentingnya. Hasil belajar siswa berpengaruh pada pencapaian kriteria ketuntasan minimal pada pembelajaran menulis surat pribadi siswa. --